Cardiovascular safety of triptans in the acute treatment of migraine - G. R. Tabeyeva (Медицинский совет, 2014)
The article highlights the issues of safety when using triptans in the treatment of migraine and the risks of cardiovascular complications. Results of a large prospective population study are provided demonstrating that triptans in patients with migraine are not associated with a significantly increased risk of cardiovascular events.